PENGARUH KUANTITAS KAPUR TERHADAP KECEPATAN TUMBUH MISELIUM JAMUR TIRAM SEBAGAI UPAYA PEMBUATAN POSTER - Mahsar Mahsar; Iwan Doddy Dharmawibawa; Masiah Masiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: White oyster mushroom cultivated by the community so that the demand for oyster mushroom growing. White oyster mushroom production in Indonesia is still lacking, it is caused by lack of optimal cultivation of oyster mushroom so it can not meet the public demand for oyster mushroom. This study aims to determine